Wyner-Ziv video coding with classified correlation noise estimation and key frame coding mode selection - Esmaili, Ghazaleh Rais (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2011)
We improve the overall rate-distortion performance of distributed video coding by efficient techniques of correlation noise estimation and key frame encoding. In existing transform-domain Wyner-Ziv video coding methods, blocks within a frame are treated uniformly to estimate the correlation noise even though the success of generating side information is different for each block. We propose a method to estimate the correlation noise by differentiating blocks within a frame based on the accuracy of the side information. Simulation results show up to 2 dB improvement over conventional methods without increasing encoder complexity. Also, in traditional Wyner-Ziv video coding, the intercorrelation of key frames is not exploited since they are simply intracoded. In this paper, we propose a frequency band coding mode selection for key frames to exploit similarities between adjacent key frames at the decoder. Simulation results show significant improvement especially for low-motion and high frame rate sequences. Furthermore, the advantage of applying both schemes in a hierarchical order is investigated. This method achieves additional improvement